La novella XI de Parabosco, posible fuente de Los esclavos libres de Lope (con la alargada sombra de Bandello al fondo). Issue 4 (2nd October 2018) - Fernández Rodríguez, Daniel
Abstract: In this article, I study a possible case of imitation between Italian and Spanish early modern literature, concerning a novella by Girolamo Parabosco (the eleventh in his Diporti ) and a play by Lope de Vega ( Los esclavos libres ). After comparing their plots, I will demarcate their common motifs, situations, and characters in order to determine the ways in which Lope de Vega could have imitated Parabosco. I will also examine the different editions of Parabosco's novels that Lope could have read in creating his play, with special attention to the possibility that the playwright may have used Il primo [-terzo] volume delle novelle del Bandello nuovamente ristampato . Finally, I study the relation between these texts and their historical context and with the so-called Byzantine romances.